A Joint Analytic Method for Estimating Aquitard Hydraulic Parameters. Issue 4 (10th January 2017) - Zhuang, Chao; Zhou, Zhifang; Illman, Walter A.
Abstract: The vertical hydraulic conductivity ( K v ), elastic ( S ske ), and inelastic ( S skv ) skeletal specific storage of aquitards are three of the most critical parameters in land subsidence investigations. Two new analytic methods are proposed to estimate the three parameters. The first analytic method is based on a new concept of delay time ratio for estimating K v and S ske of an aquitard subject to long‐term stable, cyclic hydraulic head changes at boundaries. The second analytic method estimates the S skv of the aquitard subject to linearly declining hydraulic heads at boundaries. Both methods are based on analytical solutions for flow within the aquitard, and they are jointly employed to obtain the three parameter estimates. This joint analytic method is applied to estimate the K v, S ske, and S skv of a 34.54‐m thick aquitard for which the deformation progress has been recorded by an extensometer located in Shanghai, China. The estimated results are then calibrated by PEST (Doherty 2005), a parameter estimation code coupled with a one‐dimensional aquitard‐drainage model. The K v and S ske estimated by the joint analytic method are quite close to those estimated via inverse modeling and performed much better in simulating elastic deformation than the estimates obtained from the stress‐strain diagram method of Ye and Xue (2005). The newly proposed joint analytic method is an effective tool that provides reasonable initial values for calibrating land subsidence models. Abstract : Article Impact Statement : We present a joint analytic method for estimating the hydraulic conductivity, elastic, and inelastic skeletal‐specific storage values of an aquitard.